Far-reaching effects on soil properties and underground microbial ecosystem after the introduction of black locusts in forest - Zhang, Lili; Li, Hua; Wu, Cuihua; Linghu, Gaoman; Zhu, Hengchen; Khamphilavong, Khambay; Li, Meng; Zhou, Xiaoqiang; Ma, Gangzhen; Kang, Yongxiang (Frontiers in Ecology and Evolution, 2023)
Black locust (Robinia pseudoacacia L.), a common woody afforestation species, may threaten the native biodiversity and ecosystems. Its invasive nature has not been examined in Asia, and links between aboveground and underground ecosystem have been inadequately established. Here, to figure out its effect on native ecosystems along the afforestation chronosequence, we selected three age-class mixed forests of Robinia pseudoacacia / Platycladus orientalis stands (M7, M13, and M23) and a pure native forest of Platycladus orientalis stands (P0) as the control group on the Loess Plateau in China. Results exhibited that Black locust significantly increased the shrub diversity by 23.24%, herb richness by 10.79%, total carbon by 6.14%, organic carbon by 16.05%, and total nitrogen by 36.24% in 13 years of introduction. While the decrease in the diversity and richness of shrubs and herbs, soil pH, and total phosphorus emerged after the introduction of 13 years. Despite the increasing richness and diversity of soil bacteria, total phosphorus was inferred to be a limiting factor for microbes after 23 years. The partial least squares path models showed strong correlations and remarkable aboveground-underground associations. Moreover, vegetation, the main driving force, had the most decisive influence on soil properties and microbial communities. Taken together, these results will contribute to assessments and management of black locust plantations and provide insights into the biological invasion and aboveground-underground theories.